2016
DOI: 10.1111/beer.12119
|View full text |Cite
|
Sign up to set email alerts
|

Does it really pay to be good, everywhere? A first step to understand the corporate social and financial performance link in Latin American controversial industries

Abstract: Most research studying the corporate social performance (CSP)-corporate financial performance (CFP) link has utilized developed country samples. Also, this literature has generally focused on a wide variety of industries, ignoring the fact that certain sectors -such as controversial industries -have graver social and environmental issues. Hence, a gap exists in this tradition when it comes to emerging markets and controversial industries. This paper attempts to fill this void by providing preliminary evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 111 publications
(363 reference statements)
3
84
1
9
Order By: Relevance
“…From an internal lens, we highlight the distinction made by scholars between “strategic CSR” and “corporate philanthropy” (Rodrigo et al, ; Toppinen & Korhonen‐Kurki, ). The difference lies in that the former socio‐environmental activities stem from a firm's core business and hence prioritize addressing aspects of its regular operations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From an internal lens, we highlight the distinction made by scholars between “strategic CSR” and “corporate philanthropy” (Rodrigo et al, ; Toppinen & Korhonen‐Kurki, ). The difference lies in that the former socio‐environmental activities stem from a firm's core business and hence prioritize addressing aspects of its regular operations.…”
Section: Discussionmentioning
confidence: 99%
“…Accounting research has reported that stakeholders in these sectors have greater informational needs, making companies more prone to disclose CSR reports (Grougiou et al, ; Kilian & Hennigs, ). Cai et al () argue that better social performance increases firm value, but Rodrigo, Duran, and Arenas () hint otherwise because stakeholders differ due to market‐level (business‐to‐business or business‐to‐consumer) or institutional factors (developed or emerging nation).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The environmental dimension of CSR includes ecoefficient business processes to reduce pollution, resource depletion, and environmental damage (Rodrigo et al, 2016). The extant literature suggests that innovative environmental technologies minimize operational costs, optimize energy use, improve manufacturing efficiency, and reduce costs associated with waste disposal and air pollution (Shrivastava, 1995).…”
Section: The Environmental Dimension Of Csr and Firm Valuementioning
confidence: 99%
“…There is a general concern about how companies in controversial industries gain legitimacy through their policies and initiatives related to corporate social responsibility (CSR). Rodrigo, Duran, and Arenas (2016), however, suggest that theoretical and empirical implications in non-controversial industries should not be directly applied to controversial industries. Cai, Jo, and Pan (2012), for instance, show a positive impact of CSR engagement on the firm value of American companies in eight controversial industries.…”
Section: Introductionmentioning
confidence: 99%
“…To survive in competitive environments, companies consider their stakeholders when formulating and implementing strategies or tactics at operational, business, and corporate levels (Bridoux & Stoelhorst, ; Fassin, de Colle, & Freeman, ; Menon & Yao, ; Prusty, Mohapatra, & Mukherjee, ). While the outcomes of these strategies, tactics, or actions may be good or right for one company, they may be bad or wrong for others (Epstein, Peysakhovich, & Rand, ; Rodrigo, Duran, & Arenas, ; Trevino & Nelson, ). Consequently, conflicts may emerge among groups or individuals (Smith, Gonin, & Besharov, ).…”
Section: Introductionmentioning
confidence: 99%